Development of Waqf Accounting Research: A Systematic Literature Review - Wali Saputra (Indo Publishing, 2025)
The objective of this research is to investigate the evolution of scholarly inquiries pertaining to waqf accounting through the application of a systematic literature review (SLR) methodology. A comprehensive assessment was conducted involving 58 scholarly articles published between the years 2000 and 2025, selected based on predetermined inclusion and exclusion parameters derived from the Scopus, Web of Science, and Google Scholar databases. The findings indicate a notable increase in scholarly engagement with the subject of waqf accounting over the past decade, particularly within Muslim-majority nations such as Malaysia and Indonesia. The predominant research themes encompass waqf financial reporting, the accountability of nadzir, supervisory mechanisms, and the incorporation of information technology within reporting frameworks. The majority of the studies employed a qualitative methodology, predominantly informed by theoretical frameworks such as Stakeholder Theory, Agency Theory, and Accountability Theory. Furthermore, contemporary research has begun to address issues related to the digitization of waqf accounting, particularly through the utilization of blockchain technology and smart contracts. Nevertheless, significant research gaps persist regarding the establishment of standardized reporting models and empirical investigations assessing the influence of waqf accounting on social welfare outcomes. This study advocates for the enhancement of regulatory frameworks, the augmentation of the institutional capabilities of nadzir, and the establishment of a technology-driven waqf financial reporting system. Additionally, there is a pressing need for advanced research characterized by quantitative, longitudinal, and interdisciplinary approaches to facilitate the promotion of accountable, transparent, and Sharia-compliant governance of waqf.